2005
DOI: 10.1093/ps/84.8.1321
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of slower-growing broiler genotypes grown with and without outdoor access: growth performance and carcass yield

Abstract: Consumer interest in organic and free-range poultry production is growing. An experiment was conducted to assess the impact of genotype and outdoor access on growth rate and carcass yield. One slow-growing genotype (S), 2 medium-growing genotypes (M1 and M2), and a commercial fast-growing genotype (F) were raised (straight-run) for 81, 67, and 53 d, respectively. The placement date was staggered in order to achieve a similar final body weight and each genotype was processed on the same day. Each genotype was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
134
5
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(171 citation statements)
references
References 9 publications
26
134
5
2
Order By: Relevance
“…Higher percentage of breast and thigh yields may be explained by effects of the outdoor rearing system on activity (Ponte et al 2008b) and locomotor activity (Castellini et al 2002b;Wang et al 2009). In contrast, in our results it was concluded that outdoor access did not affect carcass and part yields (Fanatico et al 2005;Wang et al 2009;Jiang et al 2011). Besides, in the outdoor group as a result of activity, abdominal fat was found to be lower than the indoor group.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Higher percentage of breast and thigh yields may be explained by effects of the outdoor rearing system on activity (Ponte et al 2008b) and locomotor activity (Castellini et al 2002b;Wang et al 2009). In contrast, in our results it was concluded that outdoor access did not affect carcass and part yields (Fanatico et al 2005;Wang et al 2009;Jiang et al 2011). Besides, in the outdoor group as a result of activity, abdominal fat was found to be lower than the indoor group.…”
Section: Discussioncontrasting
confidence: 95%
“…Broilers were individually weighed to determine slaughter weight and then were slaughtered in a processing plant of the university farm. After slaughter, broilers were scalded at 53°C for 120 s prior to plucking (Fanatico et al 2005), followed by manual evisceration. Carcasses were prechilled in water at 12°C for 15 min and chilled at 1°C for 3 h and then carcasses were weighed.…”
Section: Slaughter and Carcass Yieldmentioning
confidence: 99%
“…In contrast, the wings and necks of OC yielded more than CC, which is in agreement with the results found by Fanatico et al (2005) indicating that birds with slow-and medium-growing genotypes had higher wing yields than chickens with fast-growing genotypes. The increase in breast yield, which is the result of fast-growing genotype selection, leads to a decreased yield of other chicken parts.…”
Section: Discussionsupporting
confidence: 91%
“…Organic diets should be formulated with the organic ingredients without synthetic forms of amino acids and GMO ingredients; thus, it is crucial to formulate feed with lower quantity of soybean, which has a high risk of GMO contamination (Hanson et al, 2004), and use genotypes having lower protein and amino acids requirements (Leclercq et al, 1993;Pesti et al, 1994;Rosa et al, 2001). Slow-growing birds meet such request and are recommended for the better adaptation to the outdoor environment and to a longer rearing period (Castellini et al, 2002;Fanatico et al, 2005). In Mediterranean countries the most interesting legume alternative to soybean is the faba bean (Vicia Faba var.…”
Section: Introductionmentioning
confidence: 99%